Photoinduced electron transfer processes of functionalized nanocarbons; fullerenes, nanotubes and graphene. (1st December 2013) - D'Souza, Francis; Ito, Osamu
To solve the energy demands for a sustainable society, it is crucial to use clean solar energy. Thus, finding methods for efficient light energy conversion is an important scientific goal. For this aim, molecular devices employing composites of nanocarbons such as fullerenes, single wall carbon nanotubes (SWCNTs), and graphene are promising. In this review, we survey light-induced electron-transfer processes of these nanocarbons hybridized with photosensitizers, which have proved to be more favorable than ordinary molecules. Fullerenes connected with suitable electron donors yield characteristic long-lived radical ion pairs, suitable for constructing artificial photosynthetic systems. For SWCNTs, a combination of photosensitizers is also crucial to achieve efficient photo-induced electron transfer processes. Furthermore, in the case of diameter-sorted semi-conductive SWCNTs, each tube can be treated as a "molecule", thus, allowing molecular orbital calculations to probe the geometry as well as the electronic structures of the photosensitizer-nanotube hybrids. The two-dimensional graphene has afforded a new reaction field with a wide π-system for the attached molecules. For the confirmation of electron transfer processes, transient absorption methods in the wide wavelength regions have been used effectively. The kinetic data obtained in solution are quite useful to understand the electron transfer mechanisms, which afford useful guiding principles to construct efficient light-energy harvesting devices such as photoelectrochemical and photovoltaic solar cells.